Development of a 3-DOF Interactive Modular Robot with Human-like Head Motions - Moon, Chaerim; Yamsani, Sankalp; Kim, Joohyung (IEEE RO-MAN, 2023)
When introducing robotic systems to home environments, there are several aspects to consider such as accessibility to robotic systems and interaction capability with human subjects. Thus, in this paper, a 3-DOF robotic sensor module is suggested to embrace the concerns. It includes a handy plug-and-play feature to use one module in different spots at home. In addition, it delivers non-verbal, non-display communicative cues through human-like head motions while it is plugged into docking mounts with different states, including angled or moving. It also can track human subjects to detect and focus on users who try to interact with the robot. The performance of the robotic module was evaluated, and its compatibility with different systems was demonstrated.